Legal Protection for Financial Technology Users Against Fraud and Illegal Acts - Muhammad Labib; Rumawi Rumawi (Rechtenstudent, 2023)
Nowadays, online loan provider companies are increasing rapidly. Ironically, this has negative impacts such as crimes committed by online loan providers. So many users are harmed. This research is normative research, namely research that uses applicable laws and regulations and the approach used is a statutory approach. The results of this research are that in providing legal protection to users of online loan services, the Financial Services Authority (OJK) issued regulations, namely POJK No. 77/POJK.01/2016 concerning technology and information-based lending and borrowing services. And also POJK No.13 /POJK.02/2008 concerning digital financial innovation in the financial services sector. Legal protection can be carried out after a dispute occurs between a user and other users. This regulation is the first regulation issued by the OJK to directly protect fintech issues. The financial services authority has a very important role, namely having the authority to supervise information technology-based companies. OJK itself was formed to impact sustainable and stable economic growth. It is hoped that the OJK was formed to support the interests of the financial services sector as a whole so that it can compete in the economic sector.